Bounds on linear codes capable of detecting, locating and correcting of repeated burst errors prevailing in multiple sub-blocks - Kumar Das,Pankaj (Universidad Católica del Norte, Departamento de Matemáticas, 2020)
Abstract Linear codes are presented that can detect, locate and correct all repeated burst errors of length b or less which occur in multiple sub-blocks. We obtain lower and upper bounds on the number of check digits for the existence of these codes. Three examples, one for each type of code, are provided.